1991
DOI: 10.1007/bf00203839
|View full text |Cite
|
Sign up to set email alerts
|

Paraelectric-antiferroelectric phase transition in titanite, CaTiSiO5

Abstract: The reversible A 2/a to P2~/a phase transition (T~ = 495 K) in titanite is studied by means of electron microscopy and electron diffraction. In the low temperature phase, antiphase boundaries are frequently observed in the image. High resolution lattice imaging further allows the determination of the projected displacement vector of the antiphase boundaries to be [0 1/2 1/2]. The dynamical behaviour of these interfaces in the region close to Tc is investigated, using both diffraction contrast and high resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…The high resolution images are not able to estimate the boundary width directly, because only small orientation differences of the tetrahedra are involved. However, intermediate structures along domain boundaries are a rather widespread feature (Van Heurck et al 1991 ;Van Tendeloo et al 1976). M6ssbauer spectra of ~kermanite in which magnesium was replaced by cobalt and 5 7 F e have revealed the presence of at least 2 different environments for ions …”
Section: Discussionmentioning
confidence: 98%
“…The high resolution images are not able to estimate the boundary width directly, because only small orientation differences of the tetrahedra are involved. However, intermediate structures along domain boundaries are a rather widespread feature (Van Heurck et al 1991 ;Van Tendeloo et al 1976). M6ssbauer spectra of ~kermanite in which magnesium was replaced by cobalt and 5 7 F e have revealed the presence of at least 2 different environments for ions …”
Section: Discussionmentioning
confidence: 98%
“…Pure titanite crystallizes with the space group P2,/a ( Z = 4) and lattice parameters u = 7.069(2), b = 8.722(5), c = 6.566(8) A and /3 = 113.86(2)0 (Speer and Gibbs, 1976) at room temperature. With increasing temperature or pressure, titanite shows structural phase transitions which have been studied in much detail (Taylor and Brown, 1976;Higgins and Ribbe, 1976;Ghose et al, 1991; Van Heurck et a/., 1991; Bismayer et a/., 1992; Salje et al, 1993;Zhang et al, 1995;Kunz et al, 1996;Meyer et al, 1996;Kek et al, 1997;Chrosch et al, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…In contrast to titanite, Groat et al [9] could not detect any displacement of tin ions in malayaite and attributed this fact to the large size of the Sn 4+ ions. Insight into the energetics of the anti-ferrodistortive ordering of the tetravalent cations has recently been obtained by Kunz et al [10] in their structural investigation along the join CaTiSiO 5 ±CaSnSiO 5 . No classical phase transition has been observed in malayaite and the symmetry remains unchanged with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, Groat et al [9] found a thermal anomaly in the lattice parameters and in the unit cell volume at about 500 K. The authors explained the changes of the geometric parameters by a thermally controlled collapse of the Ca coordination without a change of the global symmetry of the structure. Part of the motivation for the present 119 Sn and 57 Fe Mo È ssbauer study of pure and iron doped CaSnSiO 5 stems from the interest in the local coordination of sublattice sites in malayaite with respect to the thermal anomaly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation